2010
DOI: 10.1007/s11999-009-1050-0
|View full text |Cite
|
Sign up to set email alerts
|

A Three-dimensional Method for Evaluating Changes in Acetabular Osteolytic Lesions in Response to Treatment

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
4
0
2
Order By: Relevance
“…Using cancellous bone chips, we achieved an average fill of 44% (range 13%-100%) of 15 treated osteolytic lesions. These results are similar to those reported by Egawa et al [21], who found an average fill of 49% (range 0%-83%) of 18 treated lesions during liner exchange. That study used the bone-graft substitute, calcium sulfate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using cancellous bone chips, we achieved an average fill of 44% (range 13%-100%) of 15 treated osteolytic lesions. These results are similar to those reported by Egawa et al [21], who found an average fill of 49% (range 0%-83%) of 18 treated lesions during liner exchange. That study used the bone-graft substitute, calcium sulfate.…”
Section: Discussionsupporting
confidence: 92%
“…In a similar study, Egawa et al [21] used preoperative and post-operative CT scans in ten patients to develop a technique for quantifying new bone mineralisation. Using a bone graft substitute, calcium sulphate, as a defect filler, it was found that an average of 24% of the original lesion volume showed evidence of new mineralisation into the void left behind once the defect filler was resorbed, and that the amount of new mineralisation at one year follow-up was directly proportional to the amount of lesion filling achieved at revision [21]. This technique supports our results, which found that lesions showing good graft incorporation tended to have a greater percentage of the lesion filled by bone-graft.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral component subsidence of between 5 and 14 mm was observed in 8 cases. At 1-year follow-up, Egawa et al (2009) found substantial new mineralization in 10 patients with symptomatic osteolysis who were treated with calcium sulfate bone graft substitute.…”
Section: Discussionmentioning
confidence: 98%
“…Früher ist davon ausgegangen worden, dass ein alleiniger Gleitpaarungswechsel die Osteolysen nicht stoppen kann. Inzwischen liegen Studien vor, die auch ohne Grafting zumindest sistierende oder minimal rückläufige Osteolysen zeigen [40,41,48,53,54], wenn der "Partikelgenerator" eliminiert wurde. Dennoch gilt Impaction Grafting mit allogenem Knochen als Standardvor allem bei stabilitätskritischen Osteolysen.…”
Section: Auffüllung Von Osteolysenunclassified
“…Die Auffüllung von Osteolysen ist nach Kürettage der Pseudomembran über die Schraubenlöcher oder über einen transossären Zugang möglich. Dabei gelingt die Osteolysenauffüllung durchschnittlich zu 43 % [54]. Besitzt die Pfanne keine Schraubenlöcher, kann ein kortikales Fenster am Os ilium ausgemeißelt werden, das allerdings die Stabilität der Pfanne nicht gefährden sollte.…”
Section: Auffüllung Von Osteolysenunclassified